Questions of Culture in Distance Learning: A Research Review - Uzuner, Sedef (International Review of Research in Open and Distributed Learning, 2009)
This paper reviews past research that focused on questions of culture in distance learning. Of specific interest are the studies that examined the influence of culture on students’ learning and engagement in asynchronous learning networks (ALNs). The purpose of this review is three-fold: to present the state of knowledge concerning the questions of culture in distance learning, to highlight important methodological issues that past research has left unresolved, and to provide practical insights into teaching culturally and linguistically diverse online communities of learners. For these purposes, 27 studies are examined and the findings are reported under the following categories: What do studies focusing on questions of culture in distance learning tell us? What implications do they suggest for practice and future research? Also, the paper provides methodological insights for researchers who wish to investigate the cultural dimensions of distance learning in future studies.